ANTIANGIOGENIC ACTIVITY OF AQUEOUS EXTRACT OF CAMELLIA SINENSIS. - PAGE AMIT B.; KULKARNI KALA S. (International Journal of Pharma and Bio Sciences, 2013)
Leaves of Camellia sinensis (CS) have been used since ancient time and are believed to have a variety of beneficial effects on human body. Recent human studies have shown that green tea may contribute to reduce risk of cardiovascular diseases and cancers. However little is known about effect of whole extract on angiogenesis in animal models. In this work, we have demonstrated antiangiogenic effects of camellia sinensis extract on three different models of angiogenesis – Chicken Chorioallentoic Membrane assay (CAM), Subcutaneous air pouch in rat (SAC) and Mesenteric window angiogenesis in rat (MWA). The extract showed dose dependent reduction in blood vessel development and nature of newly formed vessels. These effects further suggest that whole extract of C. sinensis is useful as an herbal medicine for angiogenesis dependent diseases.